Transforming Guyana's economy while combating climate change : a low-carbon development strategy : draft for consultation (The Office [Georgetown]GY, 2009)
Sets out Guyana's view on how a platform for partnership can be created where developing countries are not seen merely as passive receipients of aid, but as equal partners in the search for climate solutions. Opines that this is particularly vital in devising solutions for addressing deforestation.
Keywords: CLIMATE CHANGE